THE OUTCOME EVALUATION OF AN ACUTE ISCHAEMIC STROKE IN THE POSTERIOR REGION IN RELATION TO ROUTINE BLOOD COUNT PARAMETERS – NEUTROPHIL/LYMPHOCYTE RATIO, PLATELETCRIT AND MEAN PLATELET VOLUME - Munjiza, Dejan; Milivojević, Miloš; Vukićević, Marjana (Srpski medicinski časopis Lekarske komore, 2024)
Introduction: Acute stroke is defined as a focal or global disorder of brain function that occurs suddenly and is the third leading cause of death in the world. Depending on the mechanism of occurrence, it can be classified as acute ischemic stroke and acute hemorrhagic stroke. The work aims to examine the hypothesis that the ratio of neurtophils to lymphocytes (NLR), thrombocrit (Pct) and mean platelet volume (MVP) are significantly increased in patients with a worse outcome of a stroke in the posterior basin. Material and methods: The basis of the methodology is the analysis of laboratory data of 205 patients with ischemic stroke of the posterior basin with data on the modified Rankin score at discharge, which were adjusted into ranks for three possible treatment outcomes: good, moderately bad, and bad disease outcomes. Results: The strongest predictor of the outcome was the increase in the ratio of neutrophils and lymphocytes (NLR), which correlates with a poor outcome of the disease (p < 0,001). Thrombocrit also shows a moderate degree of association with the outcome of posterior basin ischemic stroke graded by ranks of the modified Rankin score (p = 0,002). The mean volume of platelets, in this sample of subjects, did not show either a statistical significance of the difference between the groups of patients according to the outcome of the disease graded by the ranks of the modified Rankin score, or a correlation with the outcome of the disease according to the same criterion. Conclusion: Neutrophil to lymphocyte ratio (NLR), as well as thrombocrit (Pct), are variables that, based on this study and the results from the available literature, are significantly more often elevated in patients with a worse outcome of a stroke in the posterior basin where they represent a predictor of a worse outcome of the disease.